HUBUNGAN HIPERTENSI DALAM KEHAMILAN DENGAN KEJADIAN BBLR DI RSUD WONOSARI - Putri, Puspita Sukma Dewi Pratama; Sujiyatini, Sujiyatini; Tyastuti, Siti (Poltekkes Kemenkes Yogyakarta, 2012)
Low birth weight (LBW) is still the main cause of perinatal morbidity and mortality. Hypertensive pregnancy (HP) is often the main cause of LBW incidences. ln HP, the disfunction of placenta vascular will occur and it causes the disturbance of the blood pipeline to the placenta so that the input of nutrition and embryo oxygen cannot be fulfilled optimally, and it causes the late fetus growth and LBW infant. At RSUD Wonosari in 2008, there was 30,36% woman with HP born LBW infant and the rate was getting an increase in 2009, there was 46%. Objectives: To observe the correlation between HP and LBW incidences at RSUD Wonosari in 2010-2011. Methods: The observational analytical research with case-control design, consist of HP as independent va.riable and LBW as a dependent. The samples are determined by using purposive sampling method from medical records at RSUD Wonosari in 2010-2011. The analysis method of this research is chi-square statistical test, and contingency coefficient Result: LBW incidences that were born by a woman with HP at RSUD Wonosari in 2010-2011 are about 7596, chi-square analysis with df=1 and significance level 5% produce X2 count = 39,629; p-value = 0,000, and C=0,462.